Identifying multilevel factors on student mathematics performance for Singapore, Korea, Finland, and Denmark in PISA 2022: considering individualistic versus collectivistic cultures - Jinpeng Niu; Hui Xu; Jiangtao Yu (Humanities & Social Sciences Communications)
Abstract Employing a two-level hierarchical linear modelling (HLM) analysis, the current study comparatively explored the effects of student- and school-level factors on student mathematics performance for Singapore, Korea, Finland, and Denmark in the 2022 Programme for International Student Assessment (PISA). The results showed that (a) economic, social and cultural status (ESCS), school average ESCS, mathematics self-efficacy, and mathematics anxiety are significantly associated with mathematics performance for Singapore, Korea, Finland, and Denmark; (b) mathematics teacher support has a significantly positive effect on mathematics performance for Finland and Denmark, while ability grouping for mathematics classes and student disruptive behaviours have a significantly negative impact on mathematics performance for Singapore and Korea; (c) the relationship between time in mathematics homework and mathematics performance is positive in Singapore and Korea but negative in Finland and Denmark; as well, (d) curiosity is positively related to mathematics performance for Korea, Finland, and Denmark, while the influence of mathematics motivation on mathematics performance is only significant for Finland and the influence of mathematics extra-curricular activities on mathematics performance is merely significant for Korea. In essence, the different effects may be associated with intrinsic discrepancies regarding educationally tight versus loose systems, as well as comparatively, regarding philosophically social versus individual orientations, which represent Eastern and Western cultures, respectively. The findings were discussed from a cross-cultural perspective in terms of individualism-collectivism.